2019
DOI: 10.1590/1413-81232018242.32412016
|View full text |Cite
|
Sign up to set email alerts
|

Homicídios dolosos, tráfico de drogas e indicadores sociais em Salvador, Bahia, Brasil

Abstract: Resumo O objetivo deste artigo é verificar a associação entre homicídio doloso, tráfico de drogas e indicadores sociais em Salvador, Bahia, Brasil, no ano de 2010. Trata-se de estudo ecológico a partir dos casos de homicídios dolosos e de tráfico de drogas registrados pela Polícia Civil da Bahia com indicadores sociais. A análise entre o coeficiente de homicídio doloso, tráfico de drogas e proporção de homens negros de 15 a 49 anos foi feita através do modelo de regressão binomial negativa, com software R vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
3
0
2
Order By: Relevance
“…Black Brazilians internalize their belonging to a social minority from an early age. This classification is exalted, while the opportunities are inserted as a minimum condition of survival linked to low levels of education as a factor of social and political exclusion, still being preponderant for conserving the status quo of Brazilian society, as pointed out by deep inequalities (20) .…”
Section: Discussionmentioning
confidence: 99%
“…Black Brazilians internalize their belonging to a social minority from an early age. This classification is exalted, while the opportunities are inserted as a minimum condition of survival linked to low levels of education as a factor of social and political exclusion, still being preponderant for conserving the status quo of Brazilian society, as pointed out by deep inequalities (20) .…”
Section: Discussionmentioning
confidence: 99%
“…Ousey & Lee, 2002, 2007 and 'drug trafficking ' (e.g. De Mello, 2015;Portella et al, 2019) are both used, where the term 'drug markets' tends to refer to the local area in which drug trafficking takes place, and drug trafficking to the crime itself. Further, six authors either used the term 'murder' instead of 'homicide' (Carrothers, 2016;Oguntunde et al, 2018;Stretesky et al, 2004), or used the terms interchangeably (Barber, 2000(Barber, , 2006Moore & Bergner, 2016).…”
Section: Preliminary Reflectionsmentioning
confidence: 99%
“…There were also several studies at the neighbourhood-level that specifically study the relationship between homicide and drug market activity. Portella et al (2019) use data from the Brazilian city of Salvador in 2010, and showed that, relative to neighbourhoods with low incidence of drug trafficking (< 5 incidents), neighbourhoods with high incidence of drug trafficking (> 5 incidents) reported a 34% increase in rates of homicide. Varano et al (2004) study the relationship between drug markets and the specific subtype of drug-related homicide in the city of Detroit in the United States.…”
Section: Cross-sectional Relationshipsmentioning
confidence: 99%
“…En Colombia estos son clasificados como causas de mortalidad externa (Acosta y Romero 2014). Colombia es un país que sobrepasa la media de homicidios del continente más violento del mundo (Briceño-León, Camardiel y Perdomo 2019); pero, a pesar del comportamiento anormalmente elevado de los homicidios en Colombia, estos comparten patrones con otras partes del mundo, como se concentran en las regiones metropolitanas (De León Beltrán y Garzón 2014), generalmente en sectores pobres con alta vulnerabilidad socioeconómica (McCall y Hendrix 2015; Giraldo et al 2017), y son los jóvenes del género masculino los más victimizados (Portella et al 2019), entre otras características.…”
Section: El Impacto Del Homicidio En Colombiaunclassified